Answer:
p=-6
Explanation:
the first thing to do is to add all like terms for example p+p would turn into p+p to make it so we can add them together which after we add both of those p's together we get p which now we have p+7=p+5+4 which now we add 5 and 4 which we get 9 which now the equation looks like p+7=p+9 which now we subtract 7 from 9 and we are left with 2 so now the equation is p=p+2 which now we subtract p from p and we are left with -p=2 which now we divide both sides by - which makes the equation look like p=2÷- which equals -6 so all we are left with is p=-6
5.2m questions
6.8m answers